2011
DOI: 10.1177/1010539510395121
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Health Services for Climate Change in Australia

Abstract: Objective: Whilst the implications of climate change for public health continue to be elucidated, we still require much work to guide the development of a comprehensive strategy to underpin the adaptation of the health system. Our aim is to focus on the health system responses to health risks from climate change, and in particular how best to prepare Australian health services for health risks from; heatwaves, bushfires, infectious diseases, diminished air quality and the mental health impacts of climate chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 18 publications
0
48
0
Order By: Relevance
“…Guiding principles to prepare and plan for health services in anticipation of climate change is essential to a city's sustainability. 35,36 Our study has demonstrated the need to account for weather effects and population demographics in deriving more accurate projections of the long-term demand for emergency ambulance services in Hong Kong. Collecting and promoting long-term surveillance data on morbidity caused by temperature extremes and other potential health issues will improve the characterization of weather-health relationships.…”
Section: Resultsmentioning
confidence: 98%
“…Guiding principles to prepare and plan for health services in anticipation of climate change is essential to a city's sustainability. 35,36 Our study has demonstrated the need to account for weather effects and population demographics in deriving more accurate projections of the long-term demand for emergency ambulance services in Hong Kong. Collecting and promoting long-term surveillance data on morbidity caused by temperature extremes and other potential health issues will improve the characterization of weather-health relationships.…”
Section: Resultsmentioning
confidence: 98%
“…4 Heat waves already place an enormous strain on emergency services and the health sector in general, and the added health burden due to climate change will necessitate investment in health systems coordination, personnel and infrastructure. 5 The need for adaptation is paramount to minimise present and future adverse effects of extreme heat. Health agencies need to formulate public health messages to inform the population about adaptive strategies and to ensure these are promoted by health services.…”
Section: Introductionmentioning
confidence: 99%
“…The direct and indirect health effects of climate change have been well described, both globally and for Australia 1,8,[18][19][20] (Appendix 1). The measurement and quantification of health effects will enable us to monitor the effectiveness of adaptation and mitigation strategies.…”
Section: Vulnerabilities For Sydney Lhds Arising From Climate Changementioning
confidence: 99%
“…A Above climate or levels of 1986-2005. services across administrative boundaries), strategic allocation of resources (to adapt existing services, prioritise vulnerable groups, ensure equitable access) and robustness (resilient infrastructure, consistent services, sustainable workforce). 20 It also requires a systems approach. 43 The United Nations identifies climate change as a core consideration in disaster risk management.…”
Section: Climate Change Adaptation Options For Sydney Lhdsmentioning
confidence: 99%